2021
DOI: 10.1200/cci.21.00084
|View full text |Cite
|
Sign up to set email alerts
|

My Cancer Genome: Coevolution of Precision Oncology and a Molecular Oncology Knowledgebase

Abstract: PURPOSE The My Cancer Genome (MCG) knowledgebase and resulting website were launched in 2011 with the purpose of guiding clinicians in the application of genomic testing results for treatment of patients with cancer. Both knowledgebase and website were originally developed using a wiki-style approach that relied on manual evidence curation and synthesis of that evidence into cancer-related biomarker, disease, and pathway pages on the website that summarized the literature for a clinical audience. This approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…We evaluated the processing and presentation of 10 common oncogene mutations that occur across multiple tumor types ( table 1 ). 40 41 Most mutations were cloned individually into separate retroviral ‘minigene’ vectors ( online supplemental table 1 ). The three EGFR mutations were cloned into the same retroviral construct as sequential mutated minigenes (referred to as ‘Trivalent Tandem Minigene’, or TMG) or sequential mutated exons (referred to as ‘Trivalent Tandem Exon’, or TE).…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the processing and presentation of 10 common oncogene mutations that occur across multiple tumor types ( table 1 ). 40 41 Most mutations were cloned individually into separate retroviral ‘minigene’ vectors ( online supplemental table 1 ). The three EGFR mutations were cloned into the same retroviral construct as sequential mutated minigenes (referred to as ‘Trivalent Tandem Minigene’, or TMG) or sequential mutated exons (referred to as ‘Trivalent Tandem Exon’, or TE).…”
Section: Resultsmentioning
confidence: 99%
“…In previous study, we reported that the acquired high-frequency mutation of MRE11:p.K464R in ovarian cancer patients undergoing Olaparib maintenance therapy, and preliminarily elucidate its correlation with Olaparib resistance [ 17 ]. Moreover, we did not find the record of MRE11:p.K464R mutation by searching databases (Cosmic database [ 37 ], My Cancer Genome database [ 38 ], ICGC database ( http://icgc.org ), TCGA database ( http://www.cancer.gov/ccg/research/genome-sequencing/tcga )), which strongly suggests that acquired MRE11:p.K464R mutation may play a key role in causing Olaparib resistance and may be a specific biomarker for Olaparib and even PARP inhibitor resistance. Therefore, the exploration of the mechanism of resistance caused by MRE11:p.K464R mutation will expand the understanding of PARP inhibitor resistance, and is expected to provide new ideas for the formulation of combination therapy regimens after PARP inhibitor resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the association between the expression of gene encoding Ku70 ( XRCC6 ) and survival of patients with colon and rectal adenocarcinoma were accessed from the Human Protein Atlas ( 115 ). The number of cancer cases with respect to alterations of XRCC6 and the type of alteration of XRCC6 was evaluated using the My Cancer Genome portal ( 116 ). Percentage copy number variation (amplification and deletion) in XRCC6 from patients with colon and rectal adenocarcinoma was evaluated using the Gene Set Cancer Analysis web server ( 117 ).…”
Section: Methodsmentioning
confidence: 99%